Francis O’Connor (2021), Understanding Insurgency: Popular Support for the PKK in Turkey, UK: Cambridge University Press. - Gunter, Michael M. (PARTECIPAZIONE E CONFLITTO, 2022)
For Book Review Abstrat is not required